Steel Material Stockist and Fabricator Abrasion Resistance PT. Gipan Metal Teknik Indonesia Human Resources Planning (Human Capital Plan) - Poedji Hartaty Silalahi; Rhian Indradewa; Edi Hamdi; Unggul Kustiawan (Syntax Corporation Indonesia, 2023)
PT Gipan Metal Teknik Indonesia (GMTI) is a manufacturing company that has a vision of being the best company in the field of providing and fabricating abrasion resistance steel materials, as well as a mission to prioritize product quality, timely delivery, provide the best service, and provide customized products. . Therefore, in order to support the achievement of the company's vision and mission, PT GMTI must have human resources with high competitiveness for the short, medium and long term. To achieve this, PT GMTI carries out human capital strategy and planning starting from the stages of recruiting competent employees by adapting to company needs, socializing moral guidelines as a basis for employee behavior, training and developing employee skills, to career development planning such as appointing permanent employees and career promotions. . Human resource management planning has an important role in companies in increasing work productivity to support long-term business goals and results. The success of human resource management planning is determined by the accuracy of strategy selection such as predicting company projections and maximizing human resource capabilities according to the company's organizational needs.